Promoting higher order thinking skills via teaching practices - Malini Ganapathy,; Manjet Kaur Mehar Singh,; Sarjit Kaur,; Liew, Wai Kit (Penerbit Universiti Kebangsaan Malaysia, 2017)
The birth of the Malaysia Higher Education Blueprint (2015-2025) consolidates the Ministry’s overriding aspiration to create a higher education system that ranks among the world’s leading education systems and that enables Malaysia to compete in the global economy by specifically promoting Information and Communication Technologies (ICT) and innovations that address students’ needs and enable greater personalisation of the learning experience (Ganapathy et al. 2016). This exploratory study is vital in gaining deeper insights into the current teaching and learning practices used by ESL lecturers, the types of ICT used in their classes, their views on the integration of these skills into the curriculum and the application methods of teaching and learning using ICT to promote Higher Order Thinking Skills (HOTs). Data were collected using purposive sampling where 40 participants were selected to take part in answering a questionnaire and participating in an interview. These respondents for this study comprised of a group of lecturers teaching English major degree courses in a public university in Malaysia. The findings of this study contribute a significant amount of information to the statistics of ESL teaching and learning in higher education especially in using ICT to promote HOTs. Findings from this study provide several important insights on the potential opportunities of technologies in facilitating higher order thinking but success lies on the tasks that are appropriately designed for promoting the content. This study found that ESL lecturers encounter challenges that need to be addressed in order to facilitate the learning process with the integration of ICT as a supplementary tool in promoting higher order thinking skills.